1980
DOI: 10.1159/000468423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Side Effects of Chloral Hydrate and Tryptophan as Sleeping Aids in Psychogeriatric Patients

Abstract: The effects of placebo, L-tryptophan 3 g, and chloral hydrate 500 mg on sleep were studied in 19 nonpsychotic, mildly demented, geriatric inpatients. Only chloral hydrate was more effective in inducing and maintaining sleep than placebo. Neither chloral hydrate nor L-tryptophan had any significant side effects, but withdrawal of chloral hydrate was associated with insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The present communication reports observations made to verify our clinical impression that, while LT can be an extremely effective hypnotic agent, this important action occurs in only a minority of those who receive the agent 4–5 . These pilot observations, which support this fact, form the basis for an ongoing study of biochemical factors that not only attempts to characterize LT‐responders but will, in addition, serve as a reference point in a search for clinically applicable strategies concerned with increasing an individual's hypnotic respon‐sivity to LT 6 …”
supporting
confidence: 52%
“…The present communication reports observations made to verify our clinical impression that, while LT can be an extremely effective hypnotic agent, this important action occurs in only a minority of those who receive the agent 4–5 . These pilot observations, which support this fact, form the basis for an ongoing study of biochemical factors that not only attempts to characterize LT‐responders but will, in addition, serve as a reference point in a search for clinically applicable strategies concerned with increasing an individual's hypnotic respon‐sivity to LT 6 …”
supporting
confidence: 52%
“…Chloral hydrate usually has been studied as a sedative in the elderly 136–138 . One placebo‐controlled study of chloral hydrate in a mixed patient group showed a decrease in agitation, 139 whereas two other studies reported significant problems with side effects in organic mental disorder patients during short‐term use 140 or withdrawal of the drug 141 . If agitation in the dementia patient is due to coexisting major depression, treatment with antidepressants may alleviate the behavioral problems 142,143 …”
Section: Other Drugsmentioning
confidence: 99%
“…Subjective evaluation of sleep quality was improved, but this effect did not reach statistical significance. Linnoila et al (1980) administered 3 g L-tryptophan for 7 nights to 19 female psychogeriatric inpatients, mean age of 77.4 years. Sleep was assessed by ratings made by ward nurses every 15 min.…”
Section: Questionnaire and Self-report Studiesmentioning
confidence: 99%